Projects of the Franco-Swedish Alliance against the Russian State in 1572–1575 - S. M. Ryabov (Vestnik MGIMO-Universiteta)
This article explores key aspects of the French royal court's policies in Northern Europe and the dynamics of Russian-French relations during the early 1570s. The first section provides a concise overview of the geopolitical situation in the Baltic region following the Russian-Lithuanian truce on June 24, 1570, and the Treaty of Stettin on December 13, 1570. The second section focuses on the conspiracy to overthrow King John III of Sweden, orchestrated by Charles de Mornay with support from the House of Valois. The author also examines the proposal for a Franco-Swedish alliance, articulated by Charles de Danzay, the French ambassador to Denmark. It is hypothesized that this alliance plan was opposed by Henry of Anjou, King of Poland and Grand Duke of Lithuania, who sought to avoid direct conflict with the Russian state. The third section analyzes the decline of French influence in the Baltic region during 1574–1575, attributed to Henry de Valois' flight from Poland in the summer of 1574 and the cessation of matrimonial negotiations with the Swedish Vasa dynasty in February 1575. The article delves into Charles de Danzay's political project to transform Livonia into a French vassal duchy under François of Alençon, as well as his broader vision for a FrancoDanish-Swedish-Livonian-Polish-Lithuanian alliance. The analysis demonstrates that, despite the temporary alignment of the Russian state with forces opposed to the French kingdom, the gradual expansion of mutually beneficial trade relations and dialogue in the context of Baltic policies mitigated the potential for escalating confrontation. By the mid-1570s, conditions were increasingly favorable for Russia and France to pursue shared interests, highlighting the potential for cooperative engagement over outright rivalry.